TEACHING PRAXIS AND ABSENTEEISM IN YOUTH AND ADULT EDUCATION: A SYSTEMATIC REVIEW (2020-2026) - Urbaneja, Rubén (Sinopsis Educativa, 2026)
This research aims to analyze the incidence of teaching praxis on absenteeism processes within Youth and Adult Education (EPJA) in Latin America during the 2020-2026 period. Methodologically, a systematic literature review (SLR) was conducted under the PRISMA protocol, selecting 20 high-impact articles from databases such as Scopus, SciELO, and Redalyc. The findings reveal that absenteeism is not a voluntary dropout but a systemic expulsion derived from a "banking" teaching praxis that ignores the historicity of the adult subject and the socio-educational gaps emerging in the post-pandemic era. It is identified that the transition toward socio-formative models and the strengthening of the ethics of care act as ontological protection barriers that favor permanence. The dialectical discussion, supported by the theses of Freire and Giroux, allows us to conclude that pedagogical mediation must evolve toward a multi-contextual praxis that recognizes the student as a subject of knowledge rather than a mere recipient of technical content. In conclusion, the eradication of critical absenteeism demands a new epistemology of permanence based on the systematization of practice and the co-creation of ethical life projects. It is proposed that teachers assume the role of transformative intellectuals capable of politicizing the classroom—physical or digital—to restore the right to integral education for historically marginalized populations. These results offer a roadmap for the reconfiguration of situated teacher training policies in the region, promoting a pedagogy of presence that is resilient to the structural crises of the 21st century.